NOTARY POSITION JURIDICAL REVIEW OF AQAD MURABAHAH FINANCING IN A SYARI'AH BANK MADE IN THE FORM OF NOTARY ASSET REVIEWED FROM NOTARY OFFICE LAW - Mahdinur Mahdinur; Ramlan Yusuf Rangkuti; Mustamam Mustamam (Jurnal Ilmiah METADATA, 2021)
The demand for notary competence in mastering shari'ah laws relating to the development of sharia economics aims so that notaries can cover all activities and make sharia aqad in the form of notarial deeds that are truly in accordance with the principles of shari'a Ah. The problem in this study is how is the legal certainty of a notary deed in making aqad shari'ah in financing Murabahah at a Sharia Bank made in the form of a notarial deed in terms of the Notary Position Act? How is the notary's ability to formulate the substance of the agreement based on the aqad of sharia in the city of Banda Aceh? How are the notary's obstacles and constraints in making aqad shari'ah in the form of a notary deed?. This type of research is empirical juridical research, while the nature of the study is descriptive analysis. The research data consisted of bersumbed data from primary and secondary data. The data analysis used in this study is qualitative data analysis.Based on the results of the study, the legal certainty of a notary deed in making aqad shari'ah can be said to have no legal certainty. Where the notarial deed is made on the financing aqad at the shari'ah bank, by the notary usually included the lafaz "Bismillahirrohmanirrohim". The inclusion of lafaz is not in accordance with the standard provisions in making a notarial deed as regulated in Article 38 of the Notary Position Law. The notary's ability in formulating the substance of the agreement in making a notarial deed in the murabahah financing agreement in sharia banking in Banda Aceh city is still inadequate, considering that most notaries do not have scientific competence in the field of shari'ah because they do not study syari'ah contracts in a manner specifically when attending the notary master's education. The notary obstacles in making aqad shari'ah in the form of a notary deed are influenced by three factors, namely the substance of the law, legal structure and legal culture.